Population Abundance and Infestation Intensity of Helopeltis theivora (Hemiptera: Miridae) in Cocoa Plantations of Lima Puluh Kota Regency, Indonesia - Zahlul Ikhsan; Ade Rizki Bustiar; Yaherwandi (Universitas Andalas, 2026)
Cacao (Theobroma cacao L.) is a key tropical commodity whose productivity is significantly constrained by insect pests, particularly mirid bugs such as Helopeltis theivora. This study aimed to quantify the population abundance and infestation intensity of H. theivora and to analyze their association with agroecosystem management practices in cocoa plantations of Lima Puluh Kota Regency, West Sumatra, Indonesia. Field surveys were conducted across six villages using purposive site selection followed by random sampling of plants. Pest populations were assessed through chemical knockdown and manual collection, while infestation levels were determined using standard percentage and intensity indices. A total of 206 individuals were recorded, with nymphs (63.6%) dominating the population structure. Pest abundance ranged from 0.05 to 0.35 individuals per stem. Infestation levels varied significantly across locations, with the highest infestation percentage (51.76%) and intensity (41.13%) observed in poorly managed plantations, while the lowest values (35.89% and 31.88%) occurred in well-maintained systems. Variations in pest dynamics were strongly associated with differences in sanitation, pruning, and pesticide application. The findings highlight the critical role of agroecological management and natural enemy conservation in regulating H. theivora populations. This study provides an empirical basis for developing location-specific integrated pest management (IPM) strategies to enhance cocoa productivity in tropical agroecosystems.